2019
DOI: 10.1103/physrevc.99.025503
|View full text |Cite
|
Sign up to set email alerts
|

First ultracold neutrons produced at TRIUMF

Abstract: We installed a source for ultracold neutrons at a new, dedicated spallation target at TRIUMF. The source was originally developed in Japan and uses a superfluid-helium converter cooled to 0.9 K. During an extensive test campaign in November 2017, we extracted up to 325 000 ultracold neutrons after a one-minute irradiation of the target, over three times more than previously achieved with this source. The corresponding ultracold-neutron density in the whole production and guide volume is 5.3 cm −3 . The storage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…During the Fall 2017 campaign [8], we also confirmed that the number of UCN extracted from the UCN source is proportional to the calculated beam current (Fig. 21).…”
Section: Implementation and Experiencessupporting
confidence: 73%
See 1 more Smart Citation
“…During the Fall 2017 campaign [8], we also confirmed that the number of UCN extracted from the UCN source is proportional to the calculated beam current (Fig. 21).…”
Section: Implementation and Experiencessupporting
confidence: 73%
“…A prototype UCN source was installed directly above the target in 2017 and first results from the commissioning of the UCN source were reported in Ref. [8]. Table I shows the specifications for the kicker magnet system.…”
Section: Beamline Layoutmentioning
confidence: 99%
“…We benchmarked this simulation model against the prototype source currently in operation at TRIUMF and achieved a good match between the simulated and measured UCN yield [22]. However, large uncertainties in the simulations of UCN storage and transport could potentially mask under-or over-estimations in UCN production of as much as 30 %.…”
Section: Simulation Modelmentioning
confidence: 93%
“…[21] demonstrated that with a 3 He fridge it is possible to reach the low temperature required for a superfluidhelium source close to a neutron spallation target. This source was later moved to a new spallation target with up to 50 times more beam power (40 µA, 483 MeV, 19.3 kW) at TRIUMF [22,23]. Thanks to a fast kicker magnet [24], this spallation target can be irradiated for arbitrary durations, allowing to optimally match the irradiation time to experimental requirements and reducing the heat load whenever no UCN production is required.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing a UCN source design to allow sufficient heat removal from the UCN converter, or to allow optical or pumping access, while maintaining low UCN transport loss is a common problem, in particular for He-II based sources under high heat loads. 28,29,31,32 The heat exchanger (also due to materials typically used) will need to be in a low radiation area so unwanted heating due to activation is reduced. Sufficient space between the heat exchanger and the tungsten target will be required for shielding.…”
Section: A Heat Removal With Ucn Extraction Guidementioning
confidence: 99%